2008
DOI: 10.1111/j.1745-7599.2008.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cardiovascular risk: Early identification of insulin resistance

Abstract: Early identification of insulin-resistant individuals would allow extra time for preventive measures and may alter the progression of the development of associated cardiovascular risk. A recommendation for a treatment plan of identified insulin-resistant individuals is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Among the white and black males, 34.3% and 33.3%, respectively, had elevated BMI and blood pressure, and 31.4% and 50.0% had elevated blood pressure and TG levels in addition to high IMT (>0.741 mm). In contrast, the most prominent components in the Hispanic males and the 1 Asian male were elevated TGs and low HDL-C (40% for the 42 and these numbers may rise as obesity in the population increases. The MetS represents a clustering of easily recognized clinical conditions [2][3][4][5]13,14 that have been related to an increased risk of heart disease and stroke.…”
Section: Resultsmentioning
confidence: 89%
“…Among the white and black males, 34.3% and 33.3%, respectively, had elevated BMI and blood pressure, and 31.4% and 50.0% had elevated blood pressure and TG levels in addition to high IMT (>0.741 mm). In contrast, the most prominent components in the Hispanic males and the 1 Asian male were elevated TGs and low HDL-C (40% for the 42 and these numbers may rise as obesity in the population increases. The MetS represents a clustering of easily recognized clinical conditions [2][3][4][5]13,14 that have been related to an increased risk of heart disease and stroke.…”
Section: Resultsmentioning
confidence: 89%
“…This chain reaction need the placenta combine the progesterone with PR-B, like a positive-feedback loop, resulting in ever higher levels of progesterone, may be similar to the manifestation of insulin resistance in type 2 diabetes. 25 The current study investigated the role of DNA methylation regard to PR-B negativity in endometrial carcinoma 26 breast tumor, 18 endometriosis, 20 and so on, but this is the first study to epigenetically assess PR-B promoter hypermethylation in placenta after labor onset. In our research, we found that the PR-B gene was hypermethylated in the placenta tissues of the IL group, it is reasonable to conjecture that this gene copies were transcriptionally inactive, suggesting that…”
Section: Discussionmentioning
confidence: 99%
“…This chain reaction need the placenta combine the progesterone with PR-B, like a positive-feedback loop, resulting in ever higher levels of progesterone, may be similar to the manifestation of insulin resistance in type 2 diabetes. 25…”
Section: Discussionmentioning
confidence: 99%
“…13 However, it is important to remember that plasma insulin levels do not directly measure insulin sensitivity, and thus are a clinical guide, not a fi rm benchmark. fasting insulin level has been shown to be twice as high in women with metabolic syndrome, and may be a particularly useful lab index because it is relatively easy to do, and at a low cost.…”
Section: Pcos Phenotypesmentioning
confidence: 99%